PENGEMBANGAN MOTORIK KASAR ANAK USIA DINI MELALUI KEGIATAN TARI KREASI - Anisa Tahira; Heri Yusuf Muslihin; Taopik Rahman (LPPM Universitas Muhammadiyah Cirebon, 2022)
Childhood is a very appropriate time to train children in various gross motor skills, one of which is through dance movements. Dancing is a fun learning for children because doing these movements is a learning activity while playing. Therefore, the purpose of this study is to develop children's gross motor through dance creation activities. The method used is library research. Data collection techniques are carried out by studying sources from several reference books and journals relevant to research problems. After the required data is collected, followed by data analysis. Analysis is carried out by associating the problem with relevant theoretical concepts. The result of this study is that creative dance activities are fun for children so that they can develop their gross motor optimally.